PENGARUH ANGIN TERHADAP TINGGI GELOMBANG PADA STRUKTUR BANGUNAN BREAKWATER DI TAPAK PADERI KOTA BENGKULU - Prima Nadia; Muhammad Ali; Besperi Besperi (Inersia: Jurnal Teknik Sipil, 2019)
Tapak Paderi Beach have got many damages, such as abrasion, and sedimentation by waves. This research was made to find out wind effect as the secondary within significant wave height (Hs) and the structure of breakwater design at Tapak Paderi. This research used secondary data from the last ten years wind circulation (2002-2012) and a rising-subsiding data (May as the strongest one in 2009). The resources of data come from Meteorology and Geophysics Corporation (BMKG) II class Pulau Baai and Waskita Karya Manufactory for a dimensional data includes an illustration of breakwater construction. Also, primary data involves a report survey of wave height directly to Tapak Paderi location, Bengkulu. In accordance to the analysis, those data were obtained through the calculation of breakwater within sideway type. The calculation process resorted to worksheet program, 2,832 meters for significant wave height (Hs), and 8,399 seconds for significant period (Ts). The other calculation result is a set of wave condition which devised in the breakwater field will get breaking wave because of db>dLWL>dHWL, 5,385 meters for the peak of breakwater elevation, 6,435 meters for breakwater height, 3,867 tons for stones weight (W), 3,913 meters for peak width (B), and for the thickness of shelter layer (t) which made from three layers, 2,609 meters t1, 1,211 meters t2 ,0,446 meters for t3, and total of stones for each 10 m2 (N) is sixteen grain of stones. The last, these value have been used for redesign of sideway type.